The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14112842
|View full text |Cite
|
Sign up to set email alerts
|

Turning of Additively Manufactured Ti6Al4V: Effect of the Highly Oriented Microstructure on the Surface Integrity

Abstract: Additive manufacturing processes induce a high orientation in the microstructure of the printed part due to the strong thermal gradients developed during the process caused by the highly concentrated heat source that is used to melt the metal powder layer-by-layer. The resulting microstructural anisotropy may have an effect on the post-processing operations such as machining ones. This paper investigates the influence of the anisotropy in turning operations carried out on laser powder bed fused Ti6Al4V parts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Another study [31] investigated the influence of laser-powder bed fused (L-PBF) fabrication Stainless Steel 316 L part orientations during milling by tuning the layer thickness through the L-PBF process. Furthermore, Lizzul et al [32] studied L-PBF fabricated Ti6Al4V components using altered scanning strategies (chessboard and stripes) and improved surface integrity during turning operations while considering the layers' orientations (cylindrical (across the layers) and transverse operations (along layers)). The results showed that the unique microstructure induced by the L-PBF process affects the machinability of the material depending on the strategy of scanning and/or layers orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [31] investigated the influence of laser-powder bed fused (L-PBF) fabrication Stainless Steel 316 L part orientations during milling by tuning the layer thickness through the L-PBF process. Furthermore, Lizzul et al [32] studied L-PBF fabricated Ti6Al4V components using altered scanning strategies (chessboard and stripes) and improved surface integrity during turning operations while considering the layers' orientations (cylindrical (across the layers) and transverse operations (along layers)). The results showed that the unique microstructure induced by the L-PBF process affects the machinability of the material depending on the strategy of scanning and/or layers orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of microstructure occurs at different AM processes which thus influences surface integrity after subtractive manufacturing. Lizzul et al 14 investigated the influence of microstructure on surface integrity during turning of laser powder bed fused Ti-6Al-4V components which are fabricated by different scanning techniques. Machining was influenced by microstructural anisotropy and the effect of cryogenic cooling was more on anisotropy for assessment of surface integrity.…”
Section: Introductionmentioning
confidence: 99%